The Role of Internal Control System and Spirituality on Fraud Prevention in Village Fund Management - Dekeng Setyo Budiarto; Rochmatul Isnaeni (JAFFA, 2022)
This study examines whether the internal control system, spirituality, and community participation prevent fraud in managing village funds.This study uses a survey method by distributing questionnaires offline. The objects used are 17 villages that receive village funds in Nusawungu District, Cilacap Regency. The number of respondents in the study was 85 village officials. Hypothesis testing using a structural equation model.The results showed that the internal control system and spirituality affected fraud prevention. Furthermore, fraud prevention involves the success of village fund management. However, community participation does not affect fraud prevention.This study was limited to one area with small number of sample, so the results may not be generalizable.Several previous research findings tested the internal control system, spirituality and community participation on the successful management of village funds partially. This research builds on previous findings with the structural method.